2019
DOI: 10.1556/2066.2.2019.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to post-traumatic growth following breast cancer: Results from a randomized longitudinal clinical trial containing psychological interventions

Abstract: Purpose The purpose of this study was to explore the factors influencing post-traumatic growth in breast cancer patients during 3 years after diagnosis. Materials and methods Our longitudinal study involved 71 medium and high-risk breast cancer patients, who received special attention and either hypnosis or music psychological intervention while receiving the same chemotherapy protocol. The influences of the interventions, as well as the demographic (age, marital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Agreeing with the evidence that reflects that the diagnosis of chronic diseases has a negative psychological impact on patients [ 1 , 4 ], the descriptive statistics showed adequate levels of PTG and PEI dimensions (emotional attention, clarity, and repair) in both groups, breast cancer survivors and healthy controls. These findings are in line with studies that focus on the positive changes that occur after experiencing traumatic events [ 7 , 8 ] and show that this population can emerge stronger, developing moderate–high levels of PTG after coping with the disease diagnosis and adjuvant treatments [ 14 , 16 , 20 ]. Moreover, these results are in line with previous research indicating that breast cancer survivors manage their emotions appropriately [ 60 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Agreeing with the evidence that reflects that the diagnosis of chronic diseases has a negative psychological impact on patients [ 1 , 4 ], the descriptive statistics showed adequate levels of PTG and PEI dimensions (emotional attention, clarity, and repair) in both groups, breast cancer survivors and healthy controls. These findings are in line with studies that focus on the positive changes that occur after experiencing traumatic events [ 7 , 8 ] and show that this population can emerge stronger, developing moderate–high levels of PTG after coping with the disease diagnosis and adjuvant treatments [ 14 , 16 , 20 ]. Moreover, these results are in line with previous research indicating that breast cancer survivors manage their emotions appropriately [ 60 ].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, in a cross-sectional study developed by Sharma and Zhang [ 19 ], 80% of the 120 breast cancer patients evaluated were found to have moderate to high levels of PTG. More recently, a longitudinal investigation has shown that more than 97% of the 71 samples of breast cancer patients experienced PTG [ 20 ], suggesting that coping with this traumatic situation may facilitate PTG and future disease adjustment [ 21 , 22 , 23 ]. These results show that cognitive processing may facilitate the finding of positive meaning derived from the disease [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive psychology, which encourages facing diseases with positive attitudes, has been advocated in the last 20 years [ 15 ], and researchers have started to consider the positive benefits of traumas, such as quality of life, post-traumatic growth, social support, and well-being [ 16 , 17 ]. Approximately 30–70% of participants in various studies reported benefits from trauma [ 18 ], and 97% of women with breast cancer experienced post-traumatic growth [ 19 ]. However, most studies on positive psychology-related variables of breast cancer did not confirm the post-traumatic growth phenomena via a control group design or even by matching participants via confounding or sociodemographic variables, much less by comparisons among latent variables to avoid measurement errors.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that an individual’s experience of a traumatic event may be crucial for mental disorders or ineffectiveness in various areas of life at a later stage in every plane, both family and professional [ 32 ], because trauma causes other problems and shapes the level of satisfaction an individual derives from life. Zsigmond et al [ 33 ] found a positive relationship between coping strategies, emotional severity of post-traumatic stress symptoms, social support contribution, and post-traumatic growth; however, the association differs in relation to severity in PTSD symptoms. The authors stated that post-traumatic growth has a weak to moderate association with quality of life.…”
Section: Introductionmentioning
confidence: 99%